HUBUNGAN HEALTH LOCUS OF CONTROL DENGAN KEPATUHAN PENATALAKSANAAN DIET DM TIPE 2 DI PAGUYUBAN DM PUSKESMAS III DENPASAR UTARA - Adnyani, Ida Ayu Putu Surya; Widyanthari, Desak Made; Saputra, Kadek (Coping: Community of Publishing in Nursing; Vol 3 No 3 (2015): JURNAL EDISI SEPTEMBER-DESEMBER 2015, 2015)
Diabetes Mellitus (DM) is a heterogenic abnormality group that indicated by the increase of glucose in the blood or hyperglycemia. Hyperglycemia occurs as a result of the decline of body’s ability to respond the insulin and the decrease or failure of pancreas producing insulin. Hyperglycemia affects on the increase of blood fat level and the damage of small blood vessels in long terms will cause diabetic neuropathy and abnormality of internal vital organs including heart, kidneys, brain, alimentary canal, the five senses, etc.  Compliance of dietary management is one of the important intervention in managing diabetes mellitus type 2 and health locus of control is one of the factors that may influence such obedience. This research is aimed at eliciting the relationship between health locus of control and compliance management of diabetes mellitus type 2 dietary. This research  was  non-experimental correlational with cross-sectional design. The sample was member of the society in Puskesmas III Denpasar Utara 32 respondent with purposive sampling tehnique. Fisher test used is the p value <?, ? = 0.05. The result from this research showed that there was a significant relationship between health locus of control with compliance dietary management of diabetes mellitus type 2 with p value 0,002 (<0,05). Based on the above finding, this research is expected to be served as a reference for nurses that it is very essential to observe patient health locus of control and change patient’s control in applying diabetes mellitus type 2 dietary. The conclusion of this research is that health locus of control relates with the compliance of diabetes mellitus type 2 dietary management.
Keywords: Compliance Management of Dietary Diabetes Mellitus, Health Locus of Control